Effectiveness of Dermapen Action Using Green Belt Leaf Extract Cream (Piper betle L) On Hair Growth on The Skin Surface of Female Wistar Strain Rats (Rattus Norvegicus) - Novy Hardianti; Henny Henny; Taufik Delfian (CV. Inara, 2024)
Hair loss is a very prevalent hair issue. Hair loss is typical for all humans, but if it becomes severe, it can lead to baldness. Hair goes through a unique cycle of development and loss for each strand, and one herbal plant that has the activity of fertilizing hair growth and overcoming the problem of hair loss is green betel leaf (Piper betle L). The purpose of this study was to determine the efficacy of a derma pen utilizing green betel leaf extract cream (Piper betle L) on hair development on the skin surface of female Wistar rats (Rattus norvegicus). Betel leaves have been shown to help with issues such as hair loss. Using betel leaves regularly aids in It promotes hair growth, conditions hair, and makes it thick and long. Betel leaves can also assist with itching, dandruff, and broken ends. The polyphenol and flavonoid content in betel leaves is an antioxidant and anti-inflammatory, protecting hair from damage caused by inflammatory skin illnesses and free radicals that cause hair loss on the head.